IUCN red listing of marine macroalgal species : a South African case study - Zaloumis, Nicholas Paul (Department of Biological Sciences, 2017)
The IUCN Red List of Threatened Species is considered an important tool for conservation. However most evaluations have been restricted to terrestrial species and marine species are underrepresented. In contrast to terrestrial environments, the marine environment differs in dispersal restrictions and the difficulty of sampling. This has made it hard to gain sufficient knowledge and therefore literature on the majority of species and makes it difficult to assess the effects of disturbance on species and environments. Marine species are thought to be greatly affected by over-exploitation and by-catch. However, a large proportion of the oceans diversity is situated on the coastal region, particularly as benthic organisms. These environments are considered to be a high risk of disturbance and habitat alteration due to human activities and therefore indicate that habitat loss could result in many species disappearing. The seaweed taxa have only had a total of 75 species listed. Besides being a taxonomically difficult group, there is also very little relevant literature available for effective IUCN evaluations. This study looks at assessing (i) the effectiveness, to date, of identifying seaweed species at risk of extinction, including any fallbacks or complications that seaweed species may face during an IUCN evaluation, (ii) what procedures need to be followed during the process of the evaluation, especially when limited data is available and (iii) what species characteristics could be used to identify candidates for such an assessment. This was done using two methods, firstly by reviewing what seaweed species have been currently listed and the secondly through the form of a case study using three South African endemic species with restricted distribution. IUCN threat criteria fulfil led by species and the threat categories that they achieved were related to knowledge of species distribution for seaweed species. There was an increased degree of certainty when more literature or knowledge was available and when targeted surveys for individual species were undergone. Comprehensive studies on species population dynamics and natural population fluxes were also useful. Seaweed species with restricted dispersal are most likely to make it onto the IUCN list. There is a need for seaweed scientists to come up with a solution to tackle this lack of information. Overall the IUCN evaluation process should not need to adapt for seaweed species and that evaluations have the potential to be used as indicators of ecosystem change for a region.